Early Postoperative Exposure to High-Fat Diet Does Not Increase Long-Term Weight Loss or Fat Avoidance After Roux-en-Y Gastric Bypass in Rats - Ismaeil, Aiman; Gero, Daniel; Boyle, Christina N.; Alceste, Daniela; Taha, Osama; Spector, Alan C.; Lutz, Thomas A.; Bueter, Marco (Frontiers in Nutrition, 2022)
BACKGROUND. Bariatric surgery alters food preferences in rats and reportedly decreases desire to consume high-fat high-sugar food in humans. The aim of this study was to investigate whether early post-operative exposure to high-fat food could increase body weight loss after RYGB by triggering fat avoidance. METHODS. Male Wistar rats underwent either RYGB (n=15) or sham-operations (n=16). Preoperatively a standardized 4-choice cafeteria diet (dietary options: low-fat/low-sugar, low-fat/high-sugar, high-fat/low-sugar, high-fat/high-sugar) was offered. First, each option was available for 4 days, thereafter rats were offered the 4 options simultaneously for 3 days preoperatively. Post-surgery, 8 rats in the RYGB- and 8 in the sham-group were exposed to a high-fat content diet (Oatmeal+30% lard, OM+L) for 10 days, while 7 RYGB rats and 8 sham-rats received OM alone. From the 11th postoperative day, the 4-choice cafeteria diet was reintroduced for 55-days. The intake of all available food items, macronutrients and body weight changes were monitored over 8 weeks. Main outcomes were long-term body-weight and daily change in relative caloric intake during the postoperative cafeteria period compared to the preoperative cafeteria. RESULTS. During the first 12 days of postoperative cafeteria access, RYGB-rats exposed to OM+L had a higher mean caloric intake per day than RYGB rats exposed to OM alone (Δ10 kCal, Padj=0.004), but this difference between the RYGB groups disappeared thereafter. Consequently, in the last 33 days of the postoperative cafeteria diet, the mean body weight of the RYGB+OM+L group was higher compared to RYGB+OM (Δ51g, Padj<0.001). RYGB rats, independently from the nutritional intervention, presented a progressive decrease in daily consumption of calories from fat and increased their daily energy intake mainly from non-sugar carbohydrates. No such differences were detected in sham-operated controls exposed to low- or high fat postoperative interventions. CONCLUSION. A progressive decrease in daily fat intake over time was observed after RYGB, independently from the nutritional intervention. This finding confirms that macronutrient preferences undergo progressive changes over time after RYGB and supports the role of ingestive adaptation and learning. Early postoperative exposure to high-fat food failed to accentuate fat avoidance and did not lead to superior weight loss in the long-term.